2002
DOI: 10.1063/1.1487924
|View full text |Cite
|
Sign up to set email alerts
|

Detection efficiency of large-active-area NbN single-photon superconducting detectors in the ultraviolet to near-infrared range

Abstract: We report our studies on spectral sensitivity of meander-type, superconducting NbN thin-film single-photon detectors (SPDs), characterized by GHz counting rates of visible and near-infrared photons and negligible dark counts. Our SPDs exhibit experimentally determined quantum efficiencies ranging from ∼0.2% at the 1.55 μm wavelength to ∼70% at 0.4 μm. Spectral dependences of the detection efficiency (DE) at the 0.4 to 3.0-μm-wavelength range are presented. The exponential character of the DE dependence on wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
172
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(184 citation statements)
references
References 6 publications
10
172
2
Order By: Relevance
“…Recently, the mechanism of current dissipation in quasi-2D narrow superconducting strips has been investigated. [14][15][16] We have numerically shown that the current dissipation in quasi-2D strips may arise from phase slips that involve two distinct kinds of saddle points of the free-energy functional. 16 A critical value of strip width w c is numerically determined.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the mechanism of current dissipation in quasi-2D narrow superconducting strips has been investigated. [14][15][16] We have numerically shown that the current dissipation in quasi-2D strips may arise from phase slips that involve two distinct kinds of saddle points of the free-energy functional. 16 A critical value of strip width w c is numerically determined.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these technological advances, the fundamentals of the working principle of these detectors are poorly understood and under active investigation, both theoretically [4][5][6][7][8][9][10][11] and experimentally [12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…The device self reset to its superconducting state and the current through it recovers with the time constant L kin /50 W, where L kin is the kinetic inductance of the nanowire [83]. Superconducting detectors based on NbN nanowires operate at 2-4 K temperatures and are capable of very fast counting rates (up to GHz), low dark counts (< 1 Hz), and sensitivity from visible wavelengths to far into the infrared [68,[81][82][83][84]. While other superconducting detectors (TES), based on the bolometer principle, can also achieve low noise and high efficiency (88%) [85], they require cooling to much lower temperatures (~100 mK) and are much slo− wer (kHz−MHz).…”
Section: Single-photon Detectorsmentioning
confidence: 99%